Shape memory behavior of high strength Ni54Ti46 alloys - Karaca, H.E.; Kaya, I.; Tobe, H.; Basaran, B.; Nagasako, M.; Kainuma, R.; Chumlyakov, Y. (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2013)
Shape memory behavior of highly Ni-rich Ni54Ti46 alloys was studied after aging (550°C, 3h, furnace cooling). A sequence of phase transformations was observed and the shape memory behavior is found to be highly stress dependent. After aging, a transformation strain of 1% with low temperature hysteresis is observed under an ultra high stress level of 1500MPa in compression. Moreover, superelastic response with 3% total strain can be obtained even when high stress level of 1500MPa is applied.